Migration Patterns, Stability, and Socio-Economic Impacts in Himachal Pradesh: A Geo-Spatial Analysis - Chet Ram (Darul Yasin Al Sys, 2026)
This study analyzes district-level migration patterns in Himachal Pradesh, with particular attention to migrant volume, gender composition, duration of residence, and reasons for migration. Drawing on census data, Kangra and Shimla are identified as major destination districts, whereas remote mountainous districts such as Lahul and Spiti and Kinnaur record minimal inflows. The analysis shows that marriage is the predominant reason for female migration, accounting for nearly half of all moves, followed by employment and household relocation, while most migrants settle in rural areas and more than 50% reside for ten years or longer, indicating substantial community integration. Temporal and spatial comparisons across districts reveal considerable diversity in migrant profiles and settlement stability. The study introduces a Migration Stability Index to assess migrant permanence, providing a quantifiable measure that can inform policy design. Overall, the findings underscore the need for gender-sensitive social services and district-specific economic development programs that reflect local migration dynamics, thereby contributing to more balanced regional planning and inclusive growth in Himalayan contexts.